Silencio - Scorsese, Martin, 1942-; Neeson, Liam, 1952-; Garfield, Andrew; Driver, Adam (Barcelona Savor, 2017)
In the 17th century, two Portuguese Jesuit priests travel to Japan in an attempt to locate their mentor, who is rumored to have committed apostasy, and to propagate Catholicism.
EEUU, 2016
Andrew Garfield, Adam Driver, Liam Neeson
No recomendada a menores de 16 años
Idiomas : Castellano, inglés
Keywords: Jesuitas; Películas cinematográficas -- DVD